Novel (5-nitrofurfuryl)-substituted esters of phosphonoglycine – Their synthesis and phyto- and ecotoxicological properties. (December 2017) - Lewkowski, Jarosław; Morawska, Marta; Karpowicz, Rafał; Rychter, Piotr; Rogacz, Diana; Lewicka, Kamila
Abstract: Since aminophosphonate-based herbicides like glyphosate are currently one of the most popular and widely applied active agent in agrochemistry, there is an urgent need for searching new compounds among this family with potential herbicidal activity, but exhibiting low toxicity against surrounding environment. Six new (5-nitrofurfuryl)-derived aminophosphonates were synthesized for the first time and apart from the only one example of N -benzylamino(5-nitrofuryl)-methylphosphonic acid, it was the first time in the history, when this class of compounds was prepared. Their prospective and real biological properties have been followed up by evaluation of their preliminary ecotoxicology. They have been then investigated in aspect of their phytotoxicity against oat ( A. sativa ) and common radish ( R. sativus ) exhibiting moderate-to-severe toxicity for these plants. The significant selectivity towards radish (up to 3 times greater toxicity against radish) was observed in some cases. Title compounds were also tested in terms of their toxicity for freshwater crustaceans H. incongruens (ostracods) and marine luminescent bacteria A. fischeri . Although their harmful action on ostracods was not too much elevated, they were found to be highly toxic for bacteria. Various aspects of their ecotoxicity are discussed in this paper. Graphical abstract: Highlights: Arylamino(5-nitrofurfuryl)methylphosphonates were synthesized for the first time. All tested compounds were found phytotoxic against oat and common radish. Oat was diagnosed to be more resistant to tested aminophosphonates than radish. All aminophosphonates are moderately toxic for ostracods ( H. incongruens ). Toxicity of tested compounds against luminescent bacteria A. fischeri is very high.